Addition of Local Microorganisms (MOL) Organic Waste as Compost Bioactivator. Issue 1 (1st October 2022) - Sumiyati, S; Priyambada, I B; Zahra, S A F; Pradhana, D R; Haritsa, R T; Rahman, T; Haq, M F Q; Harjanti, A W P
Abstract: Waste is a crucial problem because it causes serious impacts in terms of social, economic, cultural, and environmental aspects. With the dominance of organic waste in the composition of waste in Indonesia, there is a potential to recycle organic waste into useful products, namely compost. Composting occurs naturally so it takes a long time and is slow, therefore bio activators such as local microorganisms (MOL) are needed that can accelerate the decomposition of organic waste. The purpose of this study was to determine the effect of the use of MOL on the quality of the compost. This research method is experimental with two treatments, the first treatment with the addition of MOL and the second treatment without MOL. The results showed that the quality of compost with the addition of MOL were temperature 30°C, pH 7.4, moisture content 47.01%, C/N ratio 9.55%, phosphate 0.208%, potassium 0.027%. Meanwhile, the quality of compost without the addition of MOL were temperature 31°C, pH 7, water content 63.49%, C/N ratio 10.54%, phosphate 0.080%, potassium 0.015%. Compost with the addition of MOL was better because it met the criteria set by SNI No. 19-7030-2004 compared to compost without MOL.